Análise do crescimento e produção para determinar a maximização da renda de plantios de paricá na região norte de Mato Grosso - Kazama, Verônica Satomi (2017)
The objective of this study was to analyze the growth and production to obtain the maximization of income of commercial plantations destined to lamination of paricá (Schizolobium parahyba var. Amazonicum (Huber x Ducke) Barneby), implanted with spacing of 3 x 3,2 m, in the Region of the State of Mato Grosso. The data were collected in two sites, bad (SR) and good (SB), in stands at two, three and four years of age, in city Guarantã do Norte. Production scenarios were created in which the modeling of growth and production considered the intrinsic growth of the species and the frequency distribution by diametric class of interest for lamination. The models used were: growth in diameter (Dap) as a function of age (I); Of crown insertion height (Hic) Dap function; And tapering for volume estimation by the 5th degree polynomial. Next, the financial scenario was elaborated through the financial criteria VPL (Net Present Value), RBC (Cost Benefit Ratio), Internal Rate of Return (IRR) and CMPr (Average Cost of Production) considering the annual interest rates of 5 , 50%, 8.75% and 13.65%. The results showed that the growth models in Dap (R²aj of 0.8341), Hic models (R²aj between 0.9666 to 0.9527) and those of grinding (the R²aj between 0.8887 to 0.9146) had Good statistical adjustments. The financial criteria of the scenarios were attractive, except for the four-year SR stands. It was observed that the maximization of production was given by the current annual increment (ICA) of the settlement to the 6th year in SR (73.60 m³/ha/year) and SB (114.67 m³ ha/year), and the financial maximization by TIR (43%) and between the 5th and the 6th year in the SB (59%). Finally, according to the production and financial scenarios, it was possible to verify that, except for the bad site at the age of four years, the paricá planting for lamination of the present study can be considered a profitable investment regardless of the quality of the site under the rates interest rate considered at work.